Queen pheromone regulates egg production in a termite - Yamamoto, Yuuka (The Royal Society, 2011)
In social insects, resource allocation is a key factor that influences colony survival and growth. Optimal allocation to queens and brood is essential for maximum colony productivity, requiring colony members to have information on the total reproductive power in colonies. However, the mechanisms regulating egg production relative to the current labour force for brood care remain poorly known. Recently, a volatile chemical was identified as a termite queen pheromone that inhibits the differentiation of new neotenic reproductives (secondary reproductives developed from nymphs or workers) in Reticulitermes speratus. The same volatile chemical is also emitted by eggs. This queen pheromone would therefore be expected to act as an honest message of the reproductive power about queens. In this study, we examined how the queen pheromone influences the reproductive rate of queens in R. speratus. We compared the number of eggs produced by each queen between groups with and without exposure to artificial queen pheromone. Exposure to the pheromone resulted in a significant decrease in egg production in both single-queen and multiple-queen groups. This is the first report supporting the role of queen pheromones as a signal regulating colony-level egg production, using synthetically derived compounds in a termite.